Introduction to Human Geography - Dorrell, David; Henderson, Joseph P. (Open textbook library., 2019)
Geography is a diverse discipline that has some sort of connection to most every other academic discipline. This connection is the spatial perspective, which essentially means if a phenomenon can be mapped, it has some kind of relationship to geography. Studying the entire world is a fascinating subject, and geographical knowledge is fundamental to a competent understanding of our world. In this chapter, you will learn what geography is as well as some of the fundamental concepts that underpin the discipline. These fundamental terms and concepts will be interwoven throughout the text, so a sound understanding of these topics is critical as you delve deeper into the chapters that follow.